2016
DOI: 10.1016/j.addbeh.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and substance use outcomes among adolescents in a school-based intervention

Abstract: The stages of change (Precontemplation, Contemplation, Preparation, Action, and Maintenance) have been well studied in adult populations. However, fewer studies have examined how the stages of change are related to adolescent substance use. Furthermore, there have been no studies that have examined how the stages of change relate to outcomes in a school-based intervention. To better capture adolescent motivation, we added an additional group to the Transtheoretical Model of Change, which we titled Coerced Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The present review did find patterns of small to moderate effects for negative and positive urgency on marijuana use and negative marijuana consequences, warranting further examination; however, data for the effects of positive and negative urgency on both marijuana use (k=1 and k=2, respectively), and negative marijuana consequences (k=3 and k=4, respectively) were limited. Thoroughly assessing other impulsivityrelated traits in research and treatment is imperative, as other studies have found that, for example, positive and negative urgency traits are more strongly related to negative substance use consequences than general use (see Stautz and Cooper, 2013 for review) and interventions targeting negative and positive urgency in adolescents significantly reduce and produce sustained effects on alcohol use and negative alcohol consequences (Serafini et al, 2016). It is likely, then, that urgency is an important factor in reducing substance use consequences, including those resulting from marijuana use in both adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The present review did find patterns of small to moderate effects for negative and positive urgency on marijuana use and negative marijuana consequences, warranting further examination; however, data for the effects of positive and negative urgency on both marijuana use (k=1 and k=2, respectively), and negative marijuana consequences (k=3 and k=4, respectively) were limited. Thoroughly assessing other impulsivityrelated traits in research and treatment is imperative, as other studies have found that, for example, positive and negative urgency traits are more strongly related to negative substance use consequences than general use (see Stautz and Cooper, 2013 for review) and interventions targeting negative and positive urgency in adolescents significantly reduce and produce sustained effects on alcohol use and negative alcohol consequences (Serafini et al, 2016). It is likely, then, that urgency is an important factor in reducing substance use consequences, including those resulting from marijuana use in both adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores reflect greater recognition, less ambivalence, and taking more steps towards change. The SOCRATES is widely used in substance abuse research, including with cannabis using populations (Serafini, Shipley, & Stewart, 2016; Simons, Clarke, Simons, & Spelman, 2016), and has demonstrated reliability and validity across settings (Campbell, 1997; Long & Hollin, 2009). Self-efficacy to resist marijuana was assessed using the Self-Efficacy Questionnaire (SEQ; Stephens, Wertz, & Roffman, 1993), which consists of a total self-efficacy score and has also been validated with marijuana abusing populations (Stephens, Wertz, & Roffman, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The only other exclusion criteria were being dis-enrolled in school between referral and the start of the intervention. Project READY has demonstrated effectiveness in reducing marijuana use and consequences up to 16 weeks postintervention in several studies (Serafini, Shipley, & Stewart, 2015;Stewart, Arlt, Felleman, Athenour, & Arger, 2015;Hall, Stewart, Arger, Athenour, & Effinger, 2014) Participants consisted of 262 students from five high schools in the greater Seattle area. Of the 262 participants, 55% were male and 36% were females.…”
Section: Participantsmentioning
confidence: 99%